An Assessment of the Academic Impact of Shock Society Members. Issue 5 (May 2018) - Milgrom, Daniel P.; Koniaris, Leonidas G.; Valsangkar, Nakul P.; Lad, Neha; Bell, Teresa M.; Wojcik, Brandon; Zimmers, Teresa A.
Abstract : ABSTRACT: Professional society membership enhances career development and productivity by offering opportunities for networking and learning about recent advances in the field. The quality and contribution of such societies can be measured in part through the academic productivity, career status, and funding success rates of their members. Here, using Scopus, NIH RePORTER, and departmental websites, we compare characteristics of the Shock Society membership to those of the top 55 NIH-funded American university and hospital-based departments of surgery. Shock Society members' mean number of publications, citations and H-indices were all significantly higher than those of non-members in surgery departments ( P  < 0.001). A higher percentage of members also have received funding from the NIH (42.5% vs. 18.5%, P  < 0.001). Regression analysis indicated that members were more likely to have NIH funding compared with non-members (OR 1.46, 95% CI 1.12–1.916). Trauma surgeons belonging to the Shock Society had a higher number of publications and greater NIH funding than those who did not (130.4 vs. 42.7, P  < 0.001; 40.4% vs. 8.5%, P  < 0.001). Aggregate academic metrics from the Shock Society were superior to those of the Association for Academic Surgery and generally for the Society of University Surgeons as well. These data indicate that the Shock Society represents a highly academic and productive group of investigators. For surgery faculty, membership is associated with greater academic productivity and career advancement. While it is difficult to ascribe causation, certainly the Shock Society might positively influence careers for its members.